2019
DOI: 10.1097/qad.0000000000002223
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety of tenofovir alafenamide vs. tenofovir disoproxil fumarate

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 36 publications
10
80
0
Order By: Relevance
“…Our study demonstrates that eGFR slopes improved in individuals who switched from TDF-to TAF-containing ART, particularly in those who experienced rapid eGFR decline or CKD while receiving TDF. These data expand clinical trial experience which has shown that TAF is associated with stable renal function, even in those with mild/moderate CKD, and a more favourable renal biomarker profile than TDF [12,13]. Moreover, TAF had been successfully used and was shown to have no significant effect on biomarkers of renal tubular function in individuals who experienced proximal tubulopathy/Fanconi syndrome while receiving TDF [16][17][18][19][20], suggesting that the renal safety of TAF extends to a broad population of people with HIV infection.…”
Section: Discussionsupporting
confidence: 74%
“…Our study demonstrates that eGFR slopes improved in individuals who switched from TDF-to TAF-containing ART, particularly in those who experienced rapid eGFR decline or CKD while receiving TDF. These data expand clinical trial experience which has shown that TAF is associated with stable renal function, even in those with mild/moderate CKD, and a more favourable renal biomarker profile than TDF [12,13]. Moreover, TAF had been successfully used and was shown to have no significant effect on biomarkers of renal tubular function in individuals who experienced proximal tubulopathy/Fanconi syndrome while receiving TDF [16][17][18][19][20], suggesting that the renal safety of TAF extends to a broad population of people with HIV infection.…”
Section: Discussionsupporting
confidence: 74%
“…Tenofovir alafenamide (TAF) is a novel tenofovir pro-drug formulation that achieves high intracellular tenofovir diphosphate concentrations despite 90% lower systemic exposures. Clinical trials have demonstrated similar rates of viral suppression compared with TDF, with reduced effects on kidney and bone biomarkers [9,10]. A clinical trial in people with HIV infection and renal impairment (creatinine clearance 30-70 mL/min) supports the use of TAF in this group and suggests that TAF is generally safe across a broad range of renal pathologies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tenofovir alafenamide (TAF), a new prodrug of TFV is stable within plasma and metabolized to TFV mostly within target cells, enabling a small amount of dosing (25mg), which results in low plasma TFV levels and is thus safer to the kidney (50) (Figure 1). High efficacy and tolerability, especially minimal renal toxicity, of TAF have been shown in phase 3 trials and other studies including those which examined treatmentnaïve patients, treatment-experienced patients, and patients with renal impairment (51)(52)(53)(54). The phase 3 study, which randomly compared the efficacy and tolerability of elvitegravir/cobicistat/emtricitabine/TAF and elvitegravir/cobicistat/emtricitabine/TDF among treatment-naïve patients showed that a median change from baseline in creatinine clearance was significantly lower with TAF (-1.6 mL/min) than TDF (-7.7 mL/min) TDF-or ABC-containing ART, those who initiated TDF-containing ART were twice as likely to develop > 10 mL/min/1.73 m 2 decrement in eGFR and ≥ 25% decrement in eGFR than those who initiated ABCcontaining ART (20).…”
Section: Tenofovir Alafenamidementioning
confidence: 95%
“…(91) at week 144 (55). Furthermore, a recent pooled analysis of 26 trials showed the renal safety of TAF over TDF by examining a total of 12,519 person-years of exposure to TAF; there were no cases of proximal renal tubulopathy or Fanconi syndrome, and significantly fewer discontinuations due to renal adverse events in the TAF group than the TDF group (51). A sub-analysis of phase 3 clinical trials, which investigated efficacy and safety of elvitegravir/cobicistat/emcticitabine/TAF extracted the data of Asians and showed comparable efficacy and safety data between Asians and non-Asians (56).…”
Section: Tenofovir Alafenamidementioning
confidence: 99%